POINT,ILLUSTRATION,EXPLANATION (PIE) STRATEGY ON STUDENTS’ CREATIVITY IN WRITING - Hidayatullah, Heri; Hanan, Ahmad; Tawali, Tawali (Jurnal Ilmiah IKIP Mataram, 2018)
This current research aims at finding out the effectiveness of Point, Illustration, Explanation (PIE) Strategy on students’ creativity in writing. The design of the research was quasi-experimental with control group pre-test-post-test design. The population was the second grade students of SMAN 1 Praya Timur consisting 87 students spread into 3 classes. A cluster random sampling technique was applied and the result was MIA 1 (29 students) that became the experimental group while MIA 2 (29 students) became the control one. A creativity writing test was distributed to obtain the research data. The result of data analysis showed that the mean score of experimental group in pre test was 8,84 and post test was 11,22 and the mean score of control group in pre test was 8,46 and post test was 9,98. Then, the value of t-test (4,06) and the t-table (1,671) at the confidence level of 0,05 (95%) inferred that the Alternative Hypothesis (Ha) was accepted and the Null Hypothesis (Ho) was rejected. In conclusion, the Point, Illustration, Explanation (PIE) Strategy is effective on the students’ creativity in writing at SMAN 1 Praya Timur.